2003
DOI: 10.1086/379969
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Visible and Infrared Spectropolarimetry of a Solar Internetwork Region

Abstract: We present the first simultaneous infrared (IR) and visible spectro-polarimetric observations of a solar internetwork region. The Fe I lines at λ6301.5 Å, λ6302.5 Å, λ15648 Å, and λ15652 Å were observed, with a lag of only 1 min, using highly sensitive spectro-polarimeters operated in two different telescopes (VTT and THEMIS at the Observatorio del Teide). Some 30% of the observed region shows IR and visible Stokes V signals above noise. These polarization signals indicate the presence of kG magnetic field str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The ME inversions of the Fe i 630 nm lines carried out by Sigwarth et al (1999) and Sánchez Almeida et al (2003a) also delivered kG fields. This remains an unsolved problem, but we note that it is possible that they were biased by the modest angular resolution of the observations, since ME inversions seem to be adequate to analyze high resolution data (Orozco Suárez et al 2007a).…”
Section: Internetwork Fields Are Weak For the Most Partmentioning
confidence: 87%
“…The ME inversions of the Fe i 630 nm lines carried out by Sigwarth et al (1999) and Sánchez Almeida et al (2003a) also delivered kG fields. This remains an unsolved problem, but we note that it is possible that they were biased by the modest angular resolution of the observations, since ME inversions seem to be adequate to analyze high resolution data (Orozco Suárez et al 2007a).…”
Section: Internetwork Fields Are Weak For the Most Partmentioning
confidence: 87%
“…This part is almost certainly magnetic, but with properties that remain elusive to our observation because of its complex magnetic topology that cancels Zeeman signals, because of the low field strengths, or both. Sánchez Almeida et al (2003) andDomínguez Cerdeña et al (2006a) show how part of these hidden fields can be revealed through MISMA inversion by analyzing Fe i infra-red lines. Even weaker fields can be inferred and diagnosed via Hanle effect (e.g., Faurobert-Scholl 1994;Bommier et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Results from the near infrared Fe  lines at 1.56 microns usually lead to the conclusion that most of the mag-netic fields in the internetwork are in the form of weak fields (see Lin, 1995;Lin & Rimmele, 1999;Khomenko et al, 2003). This result is confirmed by Mart ínez González et al (2006b) but contradicted by Sánchez Almeida et al (2003) and Dom ínguez Cerdeña et al (2006). These last three works analyze simultaneous 1.5 µm and 630 nm observations.…”
Section: Introductionmentioning
confidence: 90%